Advances and Strategies for Controlling the Quality and Safety of Postharvest Fruit. (August 2021) - Chen, Tong; Ji, Dongchao; Zhang, Zhanquan; Li, Boqiang; Qin, Guozheng; Tian, Shiping
Abstract: Fresh fruits are highly valued by consumers worldwide, owing to their delicious flavors, abundant nutrients, and health-promoting characteristics, and as such, fruits make up an important component of a healthy diet. The postharvest quality and safety of fresh fruit involve complex interactions among the fruit, environmental factors, and postharvest pathogens. Efficient regulation of fruit senescence and pathogen resistance, as well as disease-causing abilities of postharvest pathogens, is critical to understanding the fundamental mechanisms that underlie fruit quality and safety. This paper provides a comprehensive review of recent advances and currently available strategies for maintaining fruit quality and controlling major postharvest pathogens, mainly Botrytis cinerea and Penicillium expansum, which may promote sustainable and environmental-friendly development of the fruit industry.